Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve the given equation step-by-step:
The equation we need to solve is:
[tex]\[ \sqrt{x} + 6 = x \][/tex]
Step 1: Isolate the square root term.
[tex]\[ \sqrt{x} = x - 6 \][/tex]
Step 2: Square both sides to eliminate the square root.
[tex]\[ (\sqrt{x})^2 = (x - 6)^2 \][/tex]
[tex]\[ x = (x - 6)^2 \][/tex]
Step 3: Expand the right-hand side.
[tex]\[ x = x^2 - 12x + 36 \][/tex]
Step 4: Rearrange the equation to standard quadratic form.
[tex]\[ 0 = x^2 - 12x + 36 - x \][/tex]
[tex]\[ 0 = x^2 - 13x + 36 \][/tex]
Step 5: Solve the quadratic equation [tex]\(x^2 - 13x + 36 = 0\)[/tex]. We can use the quadratic formula, [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -13\)[/tex], and [tex]\(c = 36\)[/tex].
[tex]\[ x = \frac{13 \pm \sqrt{169 - 144}}{2} \][/tex]
[tex]\[ x = \frac{13 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{13 \pm 5}{2} \][/tex]
Step 6: Find the two possible solutions.
[tex]\[ x = \frac{13 + 5}{2} = 9 \][/tex]
[tex]\[ x = \frac{13 - 5}{2} = 4 \][/tex]
Step 7: Verify the solutions in the original equation to check for validity.
Check [tex]\(x = 9\)[/tex]:
[tex]\[ \sqrt{9} + 6 = 9 \][/tex]
[tex]\[ 3 + 6 = 9 \][/tex]
This is correct.
Check [tex]\(x = 4\)[/tex]:
[tex]\[ \sqrt{4} + 6 = 4 \][/tex]
[tex]\[ 2 + 6 = 8 \][/tex]
This is not correct.
Thus, the only valid solution is [tex]\(x = 9\)[/tex].
Therefore, the correct answer is:
B. 9
The equation we need to solve is:
[tex]\[ \sqrt{x} + 6 = x \][/tex]
Step 1: Isolate the square root term.
[tex]\[ \sqrt{x} = x - 6 \][/tex]
Step 2: Square both sides to eliminate the square root.
[tex]\[ (\sqrt{x})^2 = (x - 6)^2 \][/tex]
[tex]\[ x = (x - 6)^2 \][/tex]
Step 3: Expand the right-hand side.
[tex]\[ x = x^2 - 12x + 36 \][/tex]
Step 4: Rearrange the equation to standard quadratic form.
[tex]\[ 0 = x^2 - 12x + 36 - x \][/tex]
[tex]\[ 0 = x^2 - 13x + 36 \][/tex]
Step 5: Solve the quadratic equation [tex]\(x^2 - 13x + 36 = 0\)[/tex]. We can use the quadratic formula, [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -13\)[/tex], and [tex]\(c = 36\)[/tex].
[tex]\[ x = \frac{13 \pm \sqrt{169 - 144}}{2} \][/tex]
[tex]\[ x = \frac{13 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ x = \frac{13 \pm 5}{2} \][/tex]
Step 6: Find the two possible solutions.
[tex]\[ x = \frac{13 + 5}{2} = 9 \][/tex]
[tex]\[ x = \frac{13 - 5}{2} = 4 \][/tex]
Step 7: Verify the solutions in the original equation to check for validity.
Check [tex]\(x = 9\)[/tex]:
[tex]\[ \sqrt{9} + 6 = 9 \][/tex]
[tex]\[ 3 + 6 = 9 \][/tex]
This is correct.
Check [tex]\(x = 4\)[/tex]:
[tex]\[ \sqrt{4} + 6 = 4 \][/tex]
[tex]\[ 2 + 6 = 8 \][/tex]
This is not correct.
Thus, the only valid solution is [tex]\(x = 9\)[/tex].
Therefore, the correct answer is:
B. 9
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.